A 13th-century headwear fragment with metal threads from southeastern Hungary nd the Bulgarian connections of Árpád Age headdresses - Türk, Attila; Harangi, Flórián (Dissertationes Archaeologicae, 2026)
The study presents a 13th-century textile fragment interwoven with metal threads, found in 2000 in Grave 33 of Szentes-Kaján-Temetőhalom, a churchyard site in the South Great Plain. The site is situated in the northern part of Csongrád County, on the outskirts of Szentes, 13 km north of the town centre, in the area known as Kaján. It was discovered in a fairly rich churchyard that started in the early 11th century; the respective grave dates to the second half of the 13th century. Besides reporting on the technical analysis of the object, the authors are the first to argue for a Balkan origin of Árpád Age metal-threaded women’s headwear, while emphasising that such textiles—which were presumably imports in the early Kingdom of Hungary—reached the country from several directions and sources. Some pieces of gilded-silver-threaded headwear may have Western European origins, but the example from Szentes-Kaján attests to a connection with the Balkans and Bulgaria.